The rise of cochlear gene therapy - Landegger, Lukas D.; Reisinger, Ellen; Lallemend, François; Hage, Steffen R.; Grimm, Dirk; Cederroth, Christopher R. (Molecular therapy, 2025)
Recent evidence provides strong support for the safe and effective use of gene therapy in humans with hearing loss. By means of a single local injection of a set of adeno-associated virus (AAV) vectors, hearing was partially restored in several children with neurosensory nonsyndromic autosomal recessive deafness 9 (DFNB9), harboring variants in the OTOF gene. Current research focuses on refining endoscopic and transmastoid injection procedures to reduce risks of side effects, as emerging evidence suggests bidirectional fluid exchanges between the ear and the brain. Moreover, gene editing approaches and novel AAV capsids are successfully tested in animal models and will likely lead to enhanced targeting of the cochlea. Here, we cover the recent advances in cochlear gene therapy, provide an overview of the translational potential of these new approaches for existing and future clinical trials, and highlight the translational implications that remain to be determined for their application in humans.